2022
DOI: 10.1101/2022.01.25.22269816
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impaired alpha and beta modulation in response to social stimuli in children with autism spectrum disorder

Abstract: Background Early preferential attention to biological motion is a fundamental mechanism priming the development of sophisticated skills to detect and react to social stimuli. Children diagnosed with autism spectrum disorders (ASD) demonstrate reduced visual orientation towards biological motion, however, the underlying neurobiological mechanisms are unknown. Methods We measured the neural oscillations in children with ASD (n=34, mean age 3.43 years) and age and gender matched typically developing children (TD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Some researchers [49,50] proposed that this atypical neural activity may contribute to the atypical social impairments observed in ASD, as it may re ect a decreased ability to process and respond to social cues effectively [51]. And previous studies [52,53], also reported higher alpha power are in response to social stimuli such as faces and emotions, compared to TD children and positively associated with autistic trait expression [54].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers [49,50] proposed that this atypical neural activity may contribute to the atypical social impairments observed in ASD, as it may re ect a decreased ability to process and respond to social cues effectively [51]. And previous studies [52,53], also reported higher alpha power are in response to social stimuli such as faces and emotions, compared to TD children and positively associated with autistic trait expression [54].…”
Section: Discussionmentioning
confidence: 99%